2004
DOI: 10.1007/s00259-004-1558-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of co-registered respiratory-gated 99mTc-Technegas/MAA SPECT-CT images in the assessment of regional lung functional impairment in patients with lung cancer

Abstract: Detailed functional-morphological correlation on co-registered gated SPECT-CT images contributes to accurate assessment of regional functional impairment, and may be useful for surgical planning, prediction of postoperative function and assessment of external beam radiotherapy effects in patients with lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 33 publications
0
33
0
5
Order By: Relevance
“…In a recent study a significantly better alignment was yielded using respiratory gated images compared to non-gated (4.9 AE 3.1 vs. 19 AE 9.1 mm) images. Respiratory gated SPECT/CT systems are evolving in order to improve diagnostics and therapy (15). However, the present investigation focuses on today's clinical routine with ungated SPECT and CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study a significantly better alignment was yielded using respiratory gated images compared to non-gated (4.9 AE 3.1 vs. 19 AE 9.1 mm) images. Respiratory gated SPECT/CT systems are evolving in order to improve diagnostics and therapy (15). However, the present investigation focuses on today's clinical routine with ungated SPECT and CT.…”
Section: Discussionmentioning
confidence: 99%
“…Use of single photon emission computed tomography (SPECT) lung perfusion scans may enable better accuracy of nuclear medicine methods compared to the planar imaging and usefully enhance the comparability of both functional and morphological tomographic images (SPECT and CTPA) (14). To accomplish this either multimodality registration of SPECT and CT or combined imaging is suggested (15).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics are especially suitable for oncology [14,[104][105][106][107][108] where detailed anatomical localization is needed. Other investigators have reported using the higher-performance SPECT/CT systems for applications in orthopedics [129][130][131][132], infection and inflammation [133][134][135][136][137][138], pulmonary function [139,140], and endocrinology [141], where the improved anatomical localization helps identify areas of disease that can be difficult to discriminate with SPECT alone. As previously mentioned, high-resolution CT performance also can be used to define target anatomy to improve the quantitation of absolute radionuclide uptake in small lesions such as tumors or in the myocardium.…”
Section: Current Spect/ct Technologiesmentioning
confidence: 99%
“…Clinical Applications of SPECT/CT Cited Anatomical/Disease Site Radiopharmaceutical SPECT/CT Application Adrenal masses 123 I-metaiodobenzylguanidine, 75 Se-cholesterol Anatomical localization [161] Biliary leak 99m Tc-diisopropyl iminodiacetic acid Anatomical localization [141] Bone scintigraphy 99m Tc-methylene diphosphonate, 99m Tc-dicarboxypropane diphosphonate Anatomical localization, attenuation correction [162][163][164][165][166][167][168][169] Brain cancer 99m Tc-tetrofosmin Anatomical localization [170] Breast cancer 99m Tc-sestamibi Anatomical localization [171] Colorectal cancer 99m Tc-labelled macroaggregated albumin Hepatic artery infusion of chemotherapy [172] Coronary artery calcification 99m Tc-tetrofosmin Head/neck cancer L-3-123 I-iodine-alpha-methyl-tyrosine, 123 I-labeled L19(scFv)2 antibody Anatomical localization [175][176][177] Hepatic haemangioma 99m Tc-labelled red blood cells Anatomical localization [178,179] Hepatic carcinoma 99m Tc-macroaggregated albumin Anatomical localization [180] Human immunodeficiency virus (HIV) 99m Tc-sulfur colloid Anatomical localization of microbicide surrogate [138] Infection Gallium-67, 111 In-labeled leukocytes Anatomical localization [133][134][135][136] Left ventricular function 99m Tc-tetrofosmin Regional wall motion evaluation, myocardial muscle mass, ejection fraction, cardiac volumes [118] Lung (ventilation/perfusion) 99m Tc-Technegas, 99m Tc-macroaggregated albumin Anatomical localization and registration of ventilation-perfusion patterns [139,140] Lung cancer 99m Tc-sestamibi, 99m Tc-depreotide Anatomical localization [181][182]…”
mentioning
confidence: 99%
“…4 Nuclear medicine imaging methods, such as PET and SPECT, are established and still expanding methods for functional and molecular imaging. For instance, Tc-99m Technegas/macro aggregated albumin (MAA) has been used for lung cancer imaging, 5 and Tc-99m MIBI has been used for detecting breast tumor. 6 Current on-board imaging systems are limited in their functional and molecular imaging capability.…”
Section: Introductionmentioning
confidence: 99%